Luso-Canadian Exchanges in Translation Studies: Translating Linguistic Variation - Rosa, Alexandra Assis (2012)
“Translation scholars no doubt can learn much from scholars of ethnic minorities, women, minor literatures and popular literatures. Much of the most exciting work in the field is already being produced by scholars from the “smaller” countries – Belgium, the Netherlands, Israel, Czechoslovakia, and French-speaking Canada” (Gentzler 2001: 197). Several Canadian scholars have been very influential in Translation Studies. The main aim of this collaborative paper on Luso-Canadian exchanges in TS is to make a very brief presentation of how some of the most “exciting” work by Canadian scholars has been received, adopted, adapted and developed in research work and teaching by Portuguese TS scholars. Selected examples of theoretical and methodological proposals by Canadian researchers in TS will be discussed, a few studies by Portuguese scholars will be mentioned, and the operative application of these studies to translation practice and teaching will be illustrated by the presentation and analysis of short excerpts of English narrative source texts, followed by their target texts in Portuguese, as produced and commented upon by former students of the Department of English, Faculty of Letters University of Lisbon.